2013
DOI: 10.6018/analesps.29.2.148251
|View full text |Cite
|
Sign up to set email alerts
|

Propuestas teóricas en la investigación sobre acoso escolar: una revisión

Abstract: Four decades of research into peer bullying have produced an extensive body of knowledge. This work attempts to provide an integrative theoretical framework, which includes the specific theories and observations. The main aim is to organize the available knowledge in order to guide the development of effective interventions. To that end, several psychological theories are described that have been used and/or adapted with the aim of understanding peer bullying. All of them, at different ecological levels and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
16

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 74 publications
(104 reference statements)
0
26
0
16
Order By: Relevance
“…De hecho, como ya se ha demostrado, las emociones juegan un papel fundamental en cualquier situación conflictiva que se pueda producir. Es por ello, que desde hace poco más de una década, se están incorporando programas de educación emocional y social en los centros educativos, tanto a nivel nacional (Bisquerra, Soldevila, Ribes, Filella y Agulló, 2005;Güell y Muñoz, 2003;López-Cassà, 2003;Monjas 1999;Pascual y Cuadrado, 2001;Renom, 2003;Vallés y Vallès, 2000; entre muchos otros) como internacional (Olweus, 2001;Espelage y Swearer, 2004;Juvonen y Graham;2001;entre otros). En EEUU se ha creado el novedoso movimiento Collaborative for Academic, Social and Emotional Learning (CASEL), el cual empezó a aplicar programas en las escuelas norteamericanas bajo la premisa de que los problemas que afectan a la infancia y adolescencia en las escuelas son causados por dificultades a nivel social y emocional.…”
Section: Relevancia De Los Problemas Escolares De Convivenciaunclassified
“…De hecho, como ya se ha demostrado, las emociones juegan un papel fundamental en cualquier situación conflictiva que se pueda producir. Es por ello, que desde hace poco más de una década, se están incorporando programas de educación emocional y social en los centros educativos, tanto a nivel nacional (Bisquerra, Soldevila, Ribes, Filella y Agulló, 2005;Güell y Muñoz, 2003;López-Cassà, 2003;Monjas 1999;Pascual y Cuadrado, 2001;Renom, 2003;Vallés y Vallès, 2000; entre muchos otros) como internacional (Olweus, 2001;Espelage y Swearer, 2004;Juvonen y Graham;2001;entre otros). En EEUU se ha creado el novedoso movimiento Collaborative for Academic, Social and Emotional Learning (CASEL), el cual empezó a aplicar programas en las escuelas norteamericanas bajo la premisa de que los problemas que afectan a la infancia y adolescencia en las escuelas son causados por dificultades a nivel social y emocional.…”
Section: Relevancia De Los Problemas Escolares De Convivenciaunclassified
“…Los modelos explicativos actuales proponen una perspectiva ecológica para su análisis (Hong y Espelage, 2012;Postigo, González, Montoya, y Ordoñez, 2013) considerando características del clima social familiar y escolar.…”
Section: Introductionunclassified
“…Recent reviews of the epidemiological studies report rates between 10 and 33% of victims and between 5 and 13% of aggressors in the case of face-to-face bullying (Hymel & Swearer, 2015); and rates between 3.2 and 33% of cybervictims and between 1 and 29.7% of cyberaggressors in the case of cyberbullying (Garaigordobil, 2015). This variability, so large in numbers, is due to cultural and linguistic differences, the study of different types of aggression, and the use of different assessment instruments and data analysis tools, a barrier that the research of these two phenomena should overcome (Postigo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although research has paid more attention to individual variables (Postigo, González, Montoya & Ordoñez, 2013), some studies have shown interest in an ecological variable such as the context in which this phenomenon occurs: the school. Bullying is defined as aggression characterized by the intention to harm, its repetition, and the power imbalance between victim and aggressor (Olweus, 2013).…”
Section: Introductionmentioning
confidence: 99%